Favorite fairy tales told in France - Haviland, Virginia (New York : Beech Tree, 1994)
Retold from Irish storytellers
Present five tales: The beem the harp, the mouse, and the bum clock; The old hag's long leather bag; Billy Beg and the bull; the widow's lazy daughter; and Patrick O'Donnell and the leprechum.
Keywords: Fairy tales -- Ireland; Folklore -- Ireland